Dylematy oceny oddziaływania państwa na funkcjonowanie rynku - Zieliński, Kazimierz (Dilemmas Concerning the Estimation of the Government Impact on Market Performance, 2005)
The article focuses mainly on possibilities of measuring market effects of government actions. The author discusses ideas of free market existing in contemporary literature and also characterizes market as an object of action of enterprises and government. Having in mind all methodological difficulties of measuring state's role, the author suggests that the object of analysis should be:- individual parts of pricing system,- only directions of deviation of economic system instead of distance from perfect position.As the assessment criteria of individual actions the author suggests assuming: elasticity of supply and demand reactions, level of prices and effectiveness of fulfilling market functions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 37-46